PERBEDAAN KEANEKARAGAMAN JENIS IKAN BERDASARKAN MUSIM DI SUNGAI PENYERANG KECAMATAN PUDING BESAR KABUPATEN BANGKA - Dewi Dewi sari; Eva Utami; Indra Ambalika Syari (Akuatik: Jurnal Sumberdaya Perairan, 2019)
Penyerang River is one of the River found in the village Kayu Besi, Puding Besar Subdistrict, district of Bangka. Seasonal differences can also cause changes in environmental conditions in the River ecosystem so that a direct impact on the decline in species diversity of fish, and species composition. This study aims to analyze the influence of the season on the diversity of fish species found in the Penyerang River Waters. The study was carried out in January-March 2018. The study took 6 observation stations 2 in the upstream, 2 in the middle and 2 in the downstream. The fishing tools used for sampling fish are dance nets, net gill and drag. Fish sampling is done in the morning until evening and from the afternoon until the morning. The results of caught fish are 470 individuals, there are 8 families, 11 genera, and 5 species. Fish diversity index at station I= 1,461, station II =1,543, station III =1,674, station IV =1,803, station V= 1,566 and station VI= 1,873, included in the criteria classified as medium. Based on the analysis of the I One-Way Annova test for differences in seasons of the diversity of fish species, the p value> 0.05 is a 0.631 means that there is no difference.